2013
DOI: 10.1111/cbdd.12018
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Structure and Pharmacology of the Human Trace Amine‐Associated Receptor 1 (hTAAR1): Homology Modelling and Docking Studies

Abstract: Trace amine-associated receptor 1 (TAAR1) is a G protein-coupled receptor that belongs to the family of TAAR receptors and responds to a class of compounds called trace amines, such as β-phenylethylamine (β-PEA) and 3-iodothyronamine (T(1)AM). The receptor is known to have a very rich pharmacology and could be also activated by other classes of compounds, including adrenergic and serotonergic ligands. It is expected that targeting TAAR1 could provide a novel pharmacological approach to correct monoaminergic dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 30 publications
5
58
0
1
Order By: Relevance
“…8,9 These findings were supported by further homology modeling and docking studies we performed within the murine and human TAAR1 and TAAR5 receptors with respect to T 1 AM ligand 10 and were also in accordance with the key role played by a proper basic feature included in any TAAR1 ligand, as reported in literature. 11 Notably, this information was definitively validated by the mutagenesis data involving the D102 residue, reported by Reese.…”
Section: Journal Of Medicinal Chemistrysupporting
confidence: 89%
See 1 more Smart Citation
“…8,9 These findings were supported by further homology modeling and docking studies we performed within the murine and human TAAR1 and TAAR5 receptors with respect to T 1 AM ligand 10 and were also in accordance with the key role played by a proper basic feature included in any TAAR1 ligand, as reported in literature. 11 Notably, this information was definitively validated by the mutagenesis data involving the D102 residue, reported by Reese.…”
Section: Journal Of Medicinal Chemistrysupporting
confidence: 89%
“…Docking studies were performed starting from the in-house homology model of the murine TAAR1 receptor, 4 built on the X-ray structure of the human β2-adrenoreceptor (PDB ID: 3PDS), 17 following a protocol we previously discussed exploring the binding mode of other TAAR1 ligands. 8,9 Briefly, the most promising compounds were docked into the putative ligand binding site by means of the Surflex docking module implemented in Sybyl-X1.0. 18 Surflex-Dock uses an empirically derived scoring function based on the binding affinities of X-ray protein−ligand complexes.…”
Section: -(26-dimethyl-4′-nitro-[11′-biphenyl]-4-yl)acetonitrile (mentioning
confidence: 99%
“…Cichero et al [32] also revealed Asp102 (in human TAAR1 position 103) and Asn283 (in human TAAR1 position 286) as anchor points for the ligand recognition process. They suggested that T 1 AM is engaged in hydrogen bonds with Asn283 (in human TAAR1 position 286) and Asp284 (in human TAAR1 position 287) [32].…”
Section: Resultsmentioning
confidence: 99%
“…Sitedirected mutagenesis studies have identified two locations in TAAR1 transmembrane domains 6 and 7, where amino acid substitutions markedly reduce or increase methamphetamine TAAR1 activation potencies in the rat and mouse TAAR1 (Reese et al, 2014). Docking studies with a homology model for the human TAAR1 (Cichero et al, 2013(Cichero et al, , 2014 could serve to further elucidate the essential amino acids that are required for ligand binding and discover structural determinants for the TAAR1 activity or inactivity of psychoactive substances.…”
Section: Discussionmentioning
confidence: 99%